2015
DOI: 10.1021/acs.jpcc.5b04777
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Chemical Ordering in Bimetallic Nanoparticles

Abstract: The real composition of nanostructure strongly determines its properties. Especially, in some cases the bulk composition of material could be different than the surface composition due to the surface segregation. Surface segregation is a common process caused by different surface energy of elements. Moreover the surface (in the sense of first atomic layer) composition is very important knowledge in many science fields e.g. semiconductors functionalization, environmental protection or pollution remediation. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 59 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…These points require more detailed comments [ 64 ]: The good agreement with Vegard’s law suggests that the alloy phase is the only one present in the samples, i.e., that the deposits are highly homogeneous. However, the literature data show that such a conclusion should be drawn with care (see Januszewska et al [ 65 ] and the references therein). In particular, there are evidences that even in homogenous systems, the deviations from Vegard’s law are observed, and vice versa, Vegard’s law can be very well fulfilled in the case of heterogeneous materials.…”
Section: Resultsmentioning
confidence: 99%
“…These points require more detailed comments [ 64 ]: The good agreement with Vegard’s law suggests that the alloy phase is the only one present in the samples, i.e., that the deposits are highly homogeneous. However, the literature data show that such a conclusion should be drawn with care (see Januszewska et al [ 65 ] and the references therein). In particular, there are evidences that even in homogenous systems, the deviations from Vegard’s law are observed, and vice versa, Vegard’s law can be very well fulfilled in the case of heterogeneous materials.…”
Section: Resultsmentioning
confidence: 99%
“…Jurczakowski and co-workers prepared PdPt nanoparticles in neat EG by co-reduction of PdCl 2 and K 2 PtCl 4 in the absence of any other reagent, leading to nanoparticles highly aggregated as proven by TEM analyses. 99 These materials were used to study the spontaneous segregation of PdPt nanoalloys, mainly evidenced by the enhanced hydrogen solubility under ambient conditions together with XPS studies, proving a higher segregation trend than their bulk counterparts. These experimental results confirm the theoretical DFT studies reported by Barcaro et al concerning the multi-shell segregation of PdPt nano-alloys.…”
Section: Platinummentioning
confidence: 99%